Genomics of vancomycin-resistant Enterococcus faecium. Issue 7 (22nd July 2019) - Gorrie, Claire; Higgs, Charlie; Carter, Glen; Stinear, Timothy P.; Howden, Benjamin
Abstract : Vancomycin-resistant Enterococcus faecium (VREfm) is a globally significant public health threat and was listed on the World Health Organization's 2017 list of high-priority pathogens for which new treatments are urgently needed. Treatment options for invasive VREfm infections are very limited, and outcomes are often poor. Whole-genome sequencing is providing important new insights into VREfm evolution, drug resistance and hospital adaptation, and is increasingly being used to track VREfm transmission within hospitals to detect outbreaks and inform infection control practices. This mini-review provides an overview of recent data on the use of genomics to understand and respond to the global problem of VREfm.